Sport for Sustainability? The Extractives Industry, Sport, and Sustainable Development. (June 2022) - Millington, Rob; Giles, Audrey R.; van Luijk, Nicolien; Hayhurst, Lyndsay M. C.
This article investigates the intersection of three interrelated trends: first, the positioning of sport as a contributor to sustainable development, particularly in regard to the increasing corporatization of sport for development (SFD); second, the trend toward sustainable development in the extractives industry, as taken up within a corporate social responsibility (CSR) approach; and third, the intersection of SFD and CSR when mobilized in pursuit of sustainable development in Indigenous communities in Canada. To do so, we examined the sustainability documents of Rio Tinto, the largest mining and metals company in Canada, with a focus on its operations in the Canadian North that are near Indigenous communities. Based on our results, we argue that SFD programming and the CSR approaches of Rio Tinto promote forms of sustainable development that capitalize on broadened (and emptied) definitions of sustainability, which may ultimately contribute to greater forms of unsustainability.